The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1212/wnl.43.11.2280
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine withdrawal

Abstract: We prospectively investigated the effects of rate of carbamazepine (CBZ) withdrawal and CBZ level on seizure type and frequency in 12 epilepsy patients withdrawn completely from antiepileptic drugs prior to entering an investigational monotherapy trial. Patients withdrawn from CBZ rapidly (over 4 days) experienced significantly more generalized tonic-clonic seizures (GTCSs) and GTCS clusters than did those withdrawn slowly (over 10 days). Complex partial seizure (CPS) frequency did not differ between the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…With a more strict definition of three or more CPSs within 24 h than that of Mark et al (3), seizure clusters occurred in 48.3% of our patients. Whether oral, rectal, or intravenous infusion of other AEDs like DZP or PHT is better in this situation, as previously suggested (13)(14)(15)(16)(17)(18)(19)(20), deserves further study. Intravenous injection of LZP probably played a role in preventing status epilepticus, and might prolong the stay in the EMU.…”
Section: Discussionmentioning
confidence: 81%
“…With a more strict definition of three or more CPSs within 24 h than that of Mark et al (3), seizure clusters occurred in 48.3% of our patients. Whether oral, rectal, or intravenous infusion of other AEDs like DZP or PHT is better in this situation, as previously suggested (13)(14)(15)(16)(17)(18)(19)(20), deserves further study. Intravenous injection of LZP probably played a role in preventing status epilepticus, and might prolong the stay in the EMU.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, we examined whether a drug holiday would lead to less efficacy to the same drug when resumed after the drug holiday; that is, does increased seizure frequency and seizure burden contribute to poorer seizure control. Clinical observations have shown that rapid CBZ withdrawal leads to an increased seizure burden Thus it is not surprising that an abrupt worsening of seizure control was recorded after animals stabilized on 100% CBZ were abruptly switched to the placebo food (0%). We aimed to test the hypothesis that the occurrence of seizures is associated with intractability and drug resistance, that is, people whose seizures are not controlled for extended periods can find their seizures refractory to treatment upon reinitiating their therapy; in other words there is a price to pay for losing seizure control and drug holidays that result in intermittent seizures can result in drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are needed to determine if the prolonged pharmacodynamic effects are due to the pharmacokinetics of CBZ after this form of oral administration or to some other mechanism. Because the apparent rebound effect occurred after a single administration of CBZ, it seems unlikely that it reflects the classical “rebound” that has been observed when patients are withdrawn from CBZ after it has been administered for prolonged periods (Duncan et al, 1990; Malow et al, 1993; Schmidt and Loscher, 2005), but additional experiments on this phenomenon are warranted.…”
Section: Discussionmentioning
confidence: 99%